Design estratégico, jogo e criatividade: uma proposta de método processual - Machado, Rodrigo Najar (Universidade do Vale do Rio dos Sinos, 2017)
This dissertation presents a reflection on the existing relations between creativity and the processes of both design and Strategic Design. It proposes the basis for its own method towards collective creation in Strategic Design supported by resources such as play and theater games. Reflections upon the ideas of both Deleuze and Guattari such as territories, deterritorializations, reterritorializations; rhizome and body without organs are related to themes such as creativity, play, theater games, design, and Strategic Design, their processes and creative possibilities. Based on the theoretical study of these themes, a procedural method called DESIGN+PLAY is proposed. An applied practical experience is done in a group of both designers and non-designers intending on examining the repercussions of this method in working groups in Strategic Design.
Keywords: Design estratégico; Jogo; Criatividade; Processo criativo; Processos de design; Strategic design; Play; Creativity; Creative process; Design process; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial